A Looser "Canon"? Relating William Abraham's "Canon and Criterion in Christian Theology" to Biblical Interpretation - Treier, Daniel J. (Journal of theological interpretation, 2008)
In his important book, William Abraham criticizes "a long-standing misinterpretation of ecclesial canons as epistemic criteria." He also defines "canon" in such a way that Scripture is not the canon but rather one entity in a network of "materials, persons, and practices officially or semi-officially identified and set apart as a means of grace and salvation by the Christian community." This paper discerns and evaluates the entailments of Abraham's viewpoint for biblical interpretation. Although Abraham's approach offers the opportunity to explore a more classic and even Eastern Orthodox perspective, biblical and historical considerations should moderate his critique of the Western heritage. His theological emphasis on means of grace is a helpful corrective. Yet we must avoid false dichotomies between soteriology and epistemology: Regulating the church's dogmatic and ethical teaching is a crucial way in which biblical texts mediate grace. A brief example from Eccl 12:9–14 enables us to see more clearly what it means to read Scripture "canonically": one of Scripture's gracious functions is goading us to read soteriologically, yet we do so in light of the pressure exerted by the received wisdom teaching that is passed on to us through biblical texts.